Non-aqueous secondary batteries

By using a single insulating layer composed of polyvinylidene fluoride-based resin and inorganic particles in a non-aqueous secondary battery, the shortcomings of existing batteries in discharge characteristics, Coulomb efficiency and cell strength are solved, and high-reliability battery performance is achieved.

CN116134089BActive Publication Date: 2025-04-29TEIJIN LTD
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
CN202180060101.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-28
Filing Date
2021-07-27
Publication Date
2025-04-29
Estimated Expiration
2041-07-27

AI Technical Summary

Technical Problem

The existing non-aqueous secondary batteries have shortcomings in discharge characteristics, Coulomb efficiency and battery cell strength, making it difficult to achieve high reliability.

Method used

A single insulating layer consisting of polyvinylidene fluoride-based resin and inorganic particles is used. The weight average molecular weight of the polyvinylidene fluoride-based resin contained in the insulating layer is 900,000 to 1.5 million, and the mass ratio of inorganic particles is 50% to 90%. The electromotive force is obtained by doping and dedoping of lithium ions.

Benefits of technology

The discharge characteristics, Coulomb efficiency and battery cell strength of non-aqueous secondary batteries are improved, and the reliability of the battery is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116134089B_ABST
    Figure CN116134089B_ABST
Patent Text Reader

Abstract

A non-aqueous secondary battery, comprising a positive electrode, a negative electrode, an insulating layer, and an electrolyte, wherein the insulating layer is a single layer having one side in contact with the positive electrode and the other side in contact with the negative electrode, wherein: (1) the insulating layer comprises a polyvinylidene fluoride resin and inorganic particles, the weight average molecular weight of the polyvinylidene fluoride resin contained in the insulating layer is not less than 900,000 and not more than 1,500,000, and the mass ratio of the inorganic particles in the insulating layer is not less than 50% by mass and not more than 90% by mass; (2) the insulating layer comprises a resin and inorganic particles, the thickness of the insulating layer is not less than 5 μm and not more than 30 μm, and the inorganic particles comprise metal sulfate particles; or (3) the insulating layer comprises a polyvinylidene fluoride resin and inorganic particles, and the polymerization components of the polyvinylidene fluoride resin comprise vinylidene fluoride and a monomer represented by the general formula (1).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a non-aqueous secondary battery. Background Art

[0002] In a non-aqueous secondary battery, an insulating layer or a separator is used for the purpose of insulating a positive electrode from a negative electrode.

[0003] For example, Japanese Patent Publication No. 2010-056037 or Japanese Patent Publication No. 2011-108516 discloses an electrode sheet for a non-aqueous electrolyte battery, which comprises: an active material layer containing a positive electrode active material or a negative electrode active material; and a heat-resistant porous layer laminated on the active material layer, which comprises a heat-resistant polymer and an inorganic filler.

[0004] For example, Japanese Patent Publication No. 2015-191710 discloses a lithium ion secondary battery having a battery element and an outer packaging body for accommodating the battery element, wherein the battery element includes: a positive electrode; a negative electrode; a ceramic separator layer containing a fluorine-based resin and insulating inorganic particles; and a lithium ion conductive non-aqueous electrolyte.

[0005] For example, Japanese Patent Gazette No. 2016-177962 discloses a method for manufacturing a secondary battery, which has the following steps: a step of applying a diaphragm layer forming composition containing two or more resin particles with different average particle sizes on an electrode; a step of drying the diaphragm layer forming composition applied to the electrode from the coating end to form a diaphragm layer integrated with the electrode on the electrode; and a step of constructing a secondary battery using the electrode formed with the diaphragm layer, a counter electrode, and an electrolyte.

[0006] For example, Japanese Patent Application Publication No. 2017-123269 discloses a separator-electrode integrated storage element for a lithium-ion secondary battery, in which a separator, which is a porous layer containing magnesium hydroxide having an average particle size of 0.5 μm to 3.0 μm, is joined and integrated with an electrode.

[0007] For example, Japanese Patent Gazette No. 4077045 discloses a battery comprising a positive electrode, a negative electrode, and an adhesive resin layer, wherein the adhesive resin layer is arranged between the positive electrode and the negative electrode and bonds at least one of the positive electrode and the negative electrode, and in the battery, the adhesive resin layer contains a filler and a resin having an average diameter of 0.01 μm to 1 μm.

[0008] For example, Japanese Patent Gazette No. 4790880 discloses a method for manufacturing a porous diaphragm, which includes the following steps: a step of configuring a diaphragm precursor solution containing a solid granular material and a polymer binder on an electrode by screen printing; and a step of transforming the diaphragm precursor solution into a porous diaphragm in the form of a thin film.

[0009] For example, Japanese Patent No. 4988972 discloses a non-aqueous secondary battery using a separator including a porous substrate and an adhesive porous layer containing a polyvinylidene fluoride resin and having a crystal size of 1 nm to 13 nm.

[0010] For example, Japanese Patent No. 5129895 discloses a nonaqueous secondary battery using a separator including a porous substrate and an adhesive porous layer containing a polyvinylidene fluoride resin having a weight average molecular weight of 600,000 to 3,000,000 and having a porosity of 30% to 60%.

[0011] For example, Japanese Patent No. 5880555 discloses a power storage device using a separator formed of a composite material including inorganic particles and an organic binder, wherein the ratio of the pigment volume concentration to the critical pigment volume concentration is 0.7 to 1.15.

[0012] For example, Japanese Patent Gazette No. 5938523 discloses a sheet-type electrode for a secondary battery, which includes: a current collector; an electrode active material layer formed on one side of the current collector; an organic-inorganic porous layer formed on the electrode active material layer and containing inorganic particles and a binder polymer; and a porous first supporting layer formed on the organic-inorganic porous layer.

[0013] For example, Japanese Patent Gazette No. 6526359 discloses a non-aqueous secondary battery using the following separator, wherein the separator has a porous substrate and a heat-resistant porous layer, wherein the heat-resistant porous layer contains a binder resin and barium sulfate particles having an average primary particle size of not less than 0.01 μm and less than 0.30 μm, and the volume ratio of the barium sulfate particles is 50 volume % to 90 volume %.

[0014] For example, Japanese Patent Gazette No. 6597267 discloses a lithium-ion secondary battery comprising: a positive electrode having a positive electrode active material layer; a negative electrode having a negative electrode active material layer; a separator; an electrolyte; and an inorganic particle layer, wherein the inorganic particle layer is arranged between the positive electrode active material layer or the negative electrode active material layer and the separator and contains Al2O3 and polyvinylidene fluoride.

[0015] For example, International Publication No. 2018 / 212252 discloses a non-aqueous secondary battery using a separator having a porous substrate and an adhesive porous layer comprising a polyvinylidene fluoride resin, wherein the polyvinylidene fluoride resin contains vinylidene fluoride and an acrylic monomer as monomer components and has a melting point of 130° C. to 148° C. Summary of the invention

[0016] Problems to be solved by the invention

[0017] It is expected that non-aqueous secondary batteries are excellent in any of discharge characteristics, coulombic efficiency, and battery cell strength, that is, high reliability. For the insulating layer, which is one of the components constituting the non-aqueous secondary battery, in order to improve the reliability of the non-aqueous secondary battery, electrical insulation, ion permeability, adhesion to the electrode, etc. are required.

[0018] The first aspect of the present disclosure and the second aspect of the present disclosure are completed based on the above circumstances.

[0019] The first aspect of the present disclosure and the second aspect of the present disclosure aim to provide a highly reliable non-aqueous secondary battery, and an object is to achieve the aim.

[0020] In addition, it is expected that the non-aqueous secondary battery is excellent in any of the aspects of discharge characteristics, discharge capacity retention, resistance to micro short circuits, and battery cell strength, that is, high reliability. For the insulating layer, which is one of the components constituting the non-aqueous secondary battery, in order to improve the reliability of the non-aqueous secondary battery, electrical insulation, ion permeability, adhesion to the electrode, stability in the electrolyte, etc. are required.

[0021] The third aspect of the present disclosure is completed based on the above situation.

[0022] The third aspect of the present disclosure aims to provide a highly reliable non-aqueous secondary battery, and aims to achieve the aim.

[0023] Means for solving problems

[0024] The first aspect of the present disclosure includes the following aspects.

[0025] <1> A non-aqueous secondary battery comprising: a positive electrode; a negative electrode; an insulating layer, the insulating layer being a single layer having one side in contact with the positive electrode and the other side in contact with the negative electrode, and containing a polyvinylidene fluoride resin and inorganic particles; and an electrolyte.

[0026] The weight average molecular weight of the polyvinylidene fluoride resin contained in the insulating layer is 900,000 to 1,500,000.

[0027] The mass ratio of the inorganic particles in the insulating layer is 50 mass % or more and less than 90 mass %.

[0028] <2> like <1> In the non-aqueous secondary battery, the inorganic particles include at least one selected from the group consisting of metal hydroxide particles and metal sulfate particles.

[0029] <3> like <1> or <2> In the non-aqueous secondary battery, the inorganic particles contained in the insulating layer have an average primary particle size of 0.01 μm or more and less than 1.00 μm.

[0030] <4> like <1> ~ <3> The nonaqueous secondary battery according to any one of the preceding claims, wherein the insulating layer has a thickness of 5 μm to 30 μm.

[0031] <5> like <1> ~ <4> The nonaqueous secondary battery according to any one of the preceding claims, wherein the insulating layer has a porosity of 40% or more and less than 80%.

[0032] <6> like <1> ~ <5> The nonaqueous secondary battery according to any one of the preceding claims, wherein the mass per unit area of ​​the insulating layer is 4 g / m 2 Above and less than 40g / m 2 .

[0033] <7> like <1> ~ <6> The nonaqueous secondary battery described in any one of the above aspects generates electromotive force by doping and dedoping of lithium ions.

[0034] The second aspect of the present disclosure includes the following aspects.

[0035] <1> A non-aqueous secondary battery comprising: a positive electrode; a negative electrode; an insulating layer, wherein the insulating layer is a single layer having one side in contact with the positive electrode and the other side in contact with the negative electrode, and contains a polyvinylidene fluoride resin and inorganic particles, wherein the polymer components of the polyvinylidene fluoride resin include vinylidene fluoride and a monomer represented by the following general formula (1); and an electrolyte.

[0036] [Chemical formula 1]

[0037]

[0038] In the general formula (1), R 1 , R 2 and R 3 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 5 carbon atoms, a carboxyl group, or a derivative of a carboxyl group, X represents a single bond, an alkylene group having 1 to 5 carbon atoms, or an alkylene group having 1 to 5 carbon atoms having a substituent, and Y represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkyl group having 1 to 5 carbon atoms substituted with at least one hydroxyl group, an alkyl group having 1 to 5 carbon atoms substituted with at least one carboxyl group, or -ROC(=O)-(CH2) n -C(=O)-OH (R represents an alkylene group having 1 to 5 carbon atoms, and n represents an integer greater than 0).

[0039] <2> like <1> In the non-aqueous secondary battery, the inorganic particles include at least one selected from the group consisting of metal hydroxide particles and metal sulfate particles.

[0040] <3> like <1> or <2> In the non-aqueous secondary battery, the inorganic particles contained in the insulating layer have an average primary particle size of 0.01 μm or more and less than 1.00 μm.

[0041] <4> like <1> ~ <3> The nonaqueous secondary battery according to any one of the preceding claims, wherein a mass ratio of the inorganic particles in the insulating layer is 50 mass % or more and less than 90 mass %.

[0042] <5> like <1> ~ <4> The nonaqueous secondary battery according to any one of the preceding claims, wherein the insulating layer has a thickness of 5 μm to 30 μm.

[0043] <6> like <1> ~ <5> The nonaqueous secondary battery according to any one of the preceding claims, wherein the insulating layer has a porosity of 40% or more and less than 80%.

[0044] <7> like <1> ~ <6> The nonaqueous secondary battery according to any one of the preceding claims, wherein the mass per unit area of ​​the insulating layer is 4 g / m 2 Above and less than 40g / m 2 .

[0045] <8> like <1> ~ <7> The nonaqueous secondary battery described in any one of the above aspects generates electromotive force by doping and dedoping of lithium ions.

[0046] The third aspect of the present disclosure includes the following aspects.

[0047] <1> A non-aqueous secondary battery comprising: a positive electrode; a negative electrode; an insulating layer, the insulating layer being a single layer having one side in contact with the positive electrode and the other side in contact with the negative electrode, and containing a resin and inorganic particles; and an electrolyte.

[0048] The thickness of the insulating layer is not less than 5 μm and not more than 30 μm.

[0049] The inorganic particles include metal sulfate particles.

[0050] <2> like <1> In the non-aqueous secondary battery, the average primary particle size of the metal sulfate particles is not less than 0.01 μm and not more than 1.00 μm.

[0051] <3> like <1> or <2> In the non-aqueous secondary battery, the resin includes a polyvinylidene fluoride resin.

[0052] <4> like <1> ~ <3> The nonaqueous secondary battery according to any one of the preceding claims, wherein a mass ratio of the inorganic particles in the insulating layer is 50 mass % or more and less than 90 mass %.

[0053] <5> like <1> ~ <4> The nonaqueous secondary battery according to any one of the preceding claims, wherein the insulating layer has a porosity of 40% or more and less than 80%.

[0054] <6> like <1> ~ <5> The nonaqueous secondary battery according to any one of the preceding claims, wherein the mass per unit area of ​​the insulating layer is 4 g / m 2 Above and less than 40g / m 2 .

[0055] <7> like <1> ~ <6> The nonaqueous secondary battery described in any one of the above aspects generates electromotive force by doping and dedoping of lithium ions.

[0056] Effects of the Invention

[0057] According to the first aspect of the present disclosure, a highly reliable non-aqueous secondary battery can be provided.

[0058] According to the second aspect of the present disclosure, a highly reliable non-aqueous secondary battery can be provided.

[0059] According to the third aspect of the present disclosure, a highly reliable non-aqueous secondary battery can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] [ Figure 1 ] is a schematic diagram showing an embodiment example of the non-aqueous secondary battery of the present disclosure. DETAILED DESCRIPTION

[0061] The following describes the implementation methods of the present disclosure. These descriptions and examples are examples of implementation methods and do not limit the scope of the implementation methods. It should be noted that, unless otherwise specified, matters described as "of the present disclosure" or "in the present disclosure" are matters common to the first, second, and third embodiments.

[0062] In the present disclosure, "A and / or B" is synonymous with "at least one of A and B". That is, "A and / or B" means that it may be only A, only B, or a combination of A and B.

[0063] In the present disclosure, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the minimum value and the maximum value, respectively.

[0064] In the numerical range recorded in stages in this disclosure, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in this disclosure, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment.

[0065] In the present disclosure, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.

[0066] In the present disclosure, when the embodiments are described with reference to the drawings, the configuration of the embodiments is not limited to the configuration shown in the drawings. In addition, the sizes of the components in each figure are conceptual, and the relative relationship between the sizes of the components is not limited to this.

[0067] In the present disclosure, when referring to the amount of each component in a composition, if there are multiple substances belonging to each component in the composition, unless otherwise specified, it means the total amount of the multiple substances present in the composition.

[0068] In the present disclosure, particles belonging to each component may contain multiple types. When multiple types of particles belonging to each component are present in the composition, the particle size of each component refers to a value for a mixture of the multiple types of particles present in the composition unless otherwise specified.

[0069] <Non-aqueous secondary battery>

[0070] The technology of the present disclosure relates to a secondary battery in which the electrolyte does not contain water, that is, a non-aqueous secondary battery. One example of an embodiment of the non-aqueous secondary battery of the present disclosure is a lithium ion secondary battery that obtains electromotive force by doping and dedoping lithium ions.

[0071] <<Non-aqueous secondary battery of the first embodiment>>

[0072] The non-aqueous secondary battery of the first mode has a positive electrode, a negative electrode, an insulating layer, and an electrolyte. The insulating layer is a single layer with one side connected to the positive electrode and the other side connected to the negative electrode, and contains a polyvinylidene fluoride resin and inorganic particles. The weight average molecular weight of the polyvinylidene fluoride resin contained in the insulating layer is more than 900,000 and less than 1.5 million, and the mass proportion of the inorganic particles in the insulating layer is more than 50% by mass and less than 90% by mass.

[0073] Hereinafter, the “positive electrode” and the “negative electrode” are collectively referred to as an “electrode.” In addition, the “non-aqueous secondary battery of the first embodiment” is also simply referred to as a “battery.”

[0074] In the battery of the first type, the insulating layer is a single layer. Therefore, (1) there is no boundary between layers inside the insulating layer, so the resistance of the insulating layer can be suppressed to a low level, which can improve the discharge characteristics and coulombic efficiency of the battery. (2) interlayer delamination will not occur inside the insulating layer, so the coulombic efficiency and battery cell strength of the battery can be improved.

[0075] In the battery of the first aspect, the weight average molecular weight (Mw) of the polyvinylidene fluoride-based resin contained in the insulating layer is 900,000 to 1,500,000.

[0076] From the viewpoint of improving the electrical insulation of the insulating layer and suppressing the clogging of the pores of the insulating layer to make the ion permeability good and improve the discharge characteristics of the battery, the Mw of the polyvinylidene fluoride resin is more than 900,000. If the Mw of the polyvinylidene fluoride resin is less than 900,000, the electrical insulation of the insulating layer is sometimes insufficient. In addition, if the Mw of the polyvinylidene fluoride resin is less than 900,000, there is a situation where the pores of the insulating layer are blocked when heat is applied to the insulating layer when manufacturing the battery, and the discharge characteristics of the battery deteriorate.

[0077] From the viewpoint of making the insulating layer and the electrode bonded well and improving the coulombic efficiency and cell strength of the battery, the Mw of the polyvinylidene fluoride resin is 1.5 million or less. If the Mw of the polyvinylidene fluoride resin is greater than 1.5 million, the polyvinylidene fluoride resin is not easily softened when heat is applied to the insulating layer during battery manufacturing, so the insulating layer is not fully bonded to the electrode, and sometimes a gap is generated between the insulating layer and the electrode, resulting in poor coulombic efficiency and cell strength of the battery.

[0078] In the battery of the first aspect, the mass ratio of the inorganic particles in the insulating layer is 50 mass % or more and less than 90 mass %.

[0079] From the viewpoint of improving the electrical insulation of the insulating layer and improving the porosity of the insulating layer to make the ion permeability good and improve the discharge characteristics of the battery, the mass ratio of the inorganic particles in the insulating layer is more than 50 mass %. If the mass ratio of the inorganic particles in the insulating layer is less than 50 mass %, the electrical insulation of the insulating layer is sometimes insufficient. In addition, if the mass ratio of the inorganic particles in the insulating layer is less than 50 mass %, the porosity of the insulating layer is insufficient, and the discharge characteristics of the battery deteriorate.

[0080] From the perspective of improving the mechanical strength of the insulating layer, making the insulating layer and the electrode bond well, and improving the coulombic efficiency and battery cell strength of the battery, the mass ratio of the inorganic particles in the insulating layer is less than 90 mass%. If the mass ratio of the inorganic particles in the insulating layer is more than 90 mass%, sometimes gaps are generated between the insulating layer and the electrode, and the coulombic efficiency and battery cell strength of the battery deteriorate. In addition, if the mass ratio of the inorganic particles in the insulating layer is more than 90 mass%, sometimes the insulating layer becomes brittle.

[0081] The above-mentioned respective structures work together to provide a complementary effect, so that the non-aqueous secondary battery of the first embodiment is excellent in discharge characteristics, coulombic efficiency, and cell strength, and therefore has high reliability.

[0082] Hereinafter, the configuration of the nonaqueous secondary battery of the first embodiment will be described in detail.

[0083] [Positive electrode of the first embodiment]

[0084] The positive electrode includes, for example, a current collector and a positive electrode active material layer disposed on one or both surfaces of the current collector.

[0085] Examples of the current collector of the positive electrode include metal foils, and examples of the metal foils include aluminum foils, titanium foils, and stainless steel foils. The thickness of the current collector of the positive electrode is preferably 5 μm to 20 μm.

[0086] The positive electrode active material layer preferably contains a positive electrode active material and a resin. The positive electrode active material layer may further contain a conductive auxiliary agent.

[0087] Examples of the positive electrode active material include transition metal oxides containing lithium. Examples of the transition metal oxides containing lithium include LiCoO2, LiNiO2, LiMn 1 / 2 Ni 1 / 2 O2、LiCo 1 / 3 Mn 1 / 3 Ni 1 / 3 O2, LiMn2O4, LiFePO4, LiCo 1 / 2 Ni 1 / 2 O2、LiAl 1 / 4 Ni 3 / 4 O2, etc.

[0088] Examples of the resin include polyvinylidene fluoride resins and alginate.

[0089] Examples of the conductive additive include carbon materials, such as acetylene black, Ketjen black, and carbon fibers.

[0090] [Negative Electrode of the First Embodiment]

[0091] The negative electrode includes, for example, a current collector and a negative electrode active material layer disposed on one surface or both surfaces of the current collector.

[0092] Examples of the negative electrode current collector include metal foils, such as copper foils, nickel foils, and stainless steel foils. The thickness of the negative electrode current collector is preferably 5 μm to 20 μm.

[0093] The negative electrode active material layer preferably contains a negative electrode active material and a resin. The negative electrode active material layer may further contain a conductive auxiliary agent.

[0094] Examples of the negative electrode active material include materials that can electrochemically absorb lithium ions, such as carbon materials, alloys of lithium with silicon, silicon compounds, tin, aluminum, etc., and Wood's alloys.

[0095] Examples of the resin include polyvinylidene fluoride resins, styrene-butadiene copolymers, and carboxymethyl cellulose.

[0096] Examples of the conductive additive include carbon materials, such as acetylene black, Ketjen black, and carbon fibers.

[0097] [Insulating layer of the first aspect]

[0098] The insulating layer of the present disclosure is a single layer having a large number of micropores inside and having a porous structure in which these micropores are connected, so that gas or liquid can pass from one surface to the other surface.

[0099] In one embodiment of the insulating layer of the present disclosure, one surface is in contact with the positive electrode active material layer, and the other surface is in contact with the negative electrode active material layer.

[0100] The insulating layer of the first embodiment contains a polyvinylidene fluoride resin and inorganic particles. The insulating layer may contain other resins other than the polyvinylidene fluoride resin, an organic filler, and the like.

[0101] - Polyvinylidene fluoride resin of the first embodiment -

[0102] Examples of polyvinylidene fluoride resins include homopolymers of vinylidene fluoride (i.e., polyvinylidene fluoride); copolymers of vinylidene fluoride and halogen-containing monomers such as hexafluoropropylene, tetrafluoroethylene, trifluoroethylene, chlorotrifluoroethylene, vinyl fluoride, and trichloroethylene; and mixtures thereof. The polyvinylidene fluoride resins may be used alone or in combination of two or more.

[0103] As polyvinylidene fluoride resin, from the viewpoint of the adhesion of the insulating layer to the electrode, preferably a copolymer of vinylidene fluoride (VDF) and hexafluoropropylene (HFP) (VDF-HFP copolymer). In the present disclosure, VDF-HFP copolymer includes a copolymer obtained by polymerizing only VDF and HFP (referred to as a VDF-HFP binary copolymer.), and any copolymer obtained by polymerizing VDF and HFP with other monomers. As other monomers herein, for example, halogen-containing monomers such as tetrafluoroethylene, trifluoroethylene, trifluorochloroethylene, vinyl fluoride, and trichloroethylene can be cited.

[0104] By increasing or decreasing the content of the HFP unit in the VDF-HFP copolymer, the crystallinity, adhesion to the electrode active material layer, and dissolution resistance to the electrolyte solution of the copolymer can be controlled within an appropriate range.

[0105] In the VDF-HFP copolymer, the proportion of HFP in all polymer components is preferably greater than 1.0 mol%, more preferably greater than 1.5 mol%, further preferably 2.0 mol% or more, further preferably 2.2 mol% or more, preferably 7.0 mol% or less, more preferably 6.5 mol% or less, further preferably 6.0 mol% or less.

[0106] The weight average molecular weight (Mw) of the polyvinylidene fluoride-based resin contained in the insulating layer of the first embodiment is 900,000 to 1,500,000.

[0107] If the Mw of the polyvinylidene fluoride resin is 900,000 or more, the electrical insulation of the insulating layer is good, and when heat is applied to the insulating layer during battery manufacturing, clogging of the pores of the insulating layer is not likely to occur. From this viewpoint, the Mw of the polyvinylidene fluoride resin is 900,000 or more, preferably 1,000,000 or more, and more preferably 1,100,000 or more.

[0108] If the Mw of the polyvinylidene fluoride resin is 1.5 million or less, when heat is applied to the insulating layer during battery manufacturing, the insulating layer and the electrode are well bonded, and it is not easy to generate gaps between the insulating layer and the electrode. From this viewpoint, the Mw of the polyvinylidene fluoride resin is 1.5 million or less, preferably 1.4 million or less, and more preferably 1.3 million or less.

[0109] The mass ratio of the polyvinylidene fluoride-based resin in the first embodiment in the insulating layer is preferably 10% by mass to 50% by mass, more preferably 15% by mass to 50% by mass, and even more preferably 20% by mass to 50% by mass.

[0110] The content of the polyvinylidene fluoride-based resin contained in the insulating layer of the first embodiment is preferably 85 to 100 mass %, more preferably 90 to 100 mass %, and even more preferably 95 to 100 mass %, based on the total amount of all resins contained in the insulating layer.

[0111] -Other resins of the first embodiment-

[0112] The insulating layer may also include other resins except polyvinylidene fluoride resin. As other resins, for example, homopolymers or copolymers of acrylic resins, fluorine rubber, styrene-butadiene copolymers, vinyl nitrile compounds (acrylonitrile, methacrylonitrile, etc.), carboxymethyl cellulose, hydroxyalkyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, polyethers (polyethylene oxide, polypropylene oxide, etc.), polyamides, fully aromatic polyamides (also referred to as aromatic polyamides), polyimides, polyamide-imide, polysulfones, polyketones, polyetherketones, polyethersulfones, polyetherimides, and mixtures thereof may be cited.

[0113] The content of the resin other than the polyvinylidene fluoride resin contained in the insulating layer of the first embodiment is preferably 0 to 15% by mass, more preferably 0 to 10% by mass, and even more preferably 0 to 5% by mass, based on the total amount of all resins contained in the insulating layer.

[0114] -First Form of Inorganic Particles-

[0115] The shape of the inorganic particles is not limited and may be any of spherical, plate-like, needle-like, and irregular shapes. From the perspective of suppressing battery short circuits or facilitating dense filling in the insulating layer, the inorganic particles are preferably spherical or plate-like particles.

[0116] The material of the inorganic particles is not limited. As inorganic particles, metal hydroxide particles, metal sulfate particles, metal oxide particles, metal carbonate particles, metal nitride particles, metal fluoride particles, particles of clay minerals, etc. can be cited. The inorganic particles can be used alone or in combination of two or more kinds of different materials.

[0117] Examples of the metal hydroxide particles include particles of magnesium hydroxide (Mg(OH)2), aluminum hydroxide (Al(OH)3), calcium hydroxide (Ca(OH)2), nickel hydroxide (Ni(OH)2), etc. The metal hydroxide particles are preferably magnesium hydroxide particles.

[0118] Examples of metal sulfate particles include particles of barium sulfate (BaSO4), strontium sulfate (SrSO4), calcium sulfate (CaSO4), calcium sulfate dihydrate (CaSO4·2H2O), alunite (KAl3(SO4)2(OH)6), and jarosite (KFe3(SO4)2(OH)6). Preferred metal sulfate particles are barium sulfate particles.

[0119] Examples of metal oxide particles include particles of magnesium oxide, aluminum oxide (Al2O3), boehmite (AlOOH, aluminum oxide monohydrate), titanium dioxide (TiO2), silicon dioxide (SiO2), zirconium oxide (ZrO2), barium titanate (BaTiO3), zinc oxide, and the like.

[0120] Examples of the metal carbonate particles include particles of magnesium carbonate, calcium carbonate, and the like.

[0121] Examples of the metal nitride particles include particles of magnesium nitride, aluminum nitride, calcium nitride, titanium nitride, and the like.

[0122] Examples of the metal fluoride particles include particles of magnesium fluoride, calcium fluoride, and the like.

[0123] Examples of the clay mineral particles include particles of calcium silicate, calcium phosphate, apatite, talc, and the like.

[0124] As the inorganic particles, metal hydroxide particles are preferred from the viewpoint of flame retardancy, and metal sulfate particles are preferred from the viewpoint of stability with respect to the electrolyte and suppression of gas generation. The inorganic particles preferably include at least one selected from the group consisting of metal hydroxide particles and metal sulfate particles.

[0125] From the viewpoint of making the insulating layer porous and improving ion permeability, the average primary particle size of the inorganic particles contained in the insulating layer is preferably 0.01 μm or more, more preferably 0.02 μm or more, and even more preferably 0.03 μm or more.

[0126] From the viewpoint of reducing the thickness of the insulating layer and improving the energy density of the battery, the average primary particle size of the inorganic particles contained in the insulating layer is preferably less than 1.00 μm, more preferably less than 0.95 μm, and even more preferably less than 0.90 μm.

[0127] As the inorganic particles, two or more inorganic particles having different average primary particle sizes may be used in combination. In this case, it is preferred that the average primary particle size of each of the inorganic particles is within the above range, and it is preferred that the overall average primary particle size is within the above range.

[0128] The average primary particle size of the inorganic particles is obtained by measuring the major diameters of 100 randomly selected primary particles in the observation based on a scanning electron microscope (SEM), and averaging the 100 major diameters. In the case where the primary particle size of the inorganic particles is small and it is difficult to measure the major diameter of the primary particles using SEM, and / or the inorganic particles are significantly aggregated and it is difficult to measure the major diameter of the primary particles using SEM, the BET specific surface area (m 2 / g) and the average primary particle size was determined according to the following formula assuming that the inorganic particles were spherical.

[0129] Average primary particle size (μm) = 6 ÷ [specific gravity (g / cm 3 )×BET specific surface area (m 2 / g)]

[0130] BET specific surface area (m 2 / g) is determined by the BET multipoint method which is a gas adsorption method using nitrogen gas. When measuring by the gas adsorption method, nitrogen gas is adsorbed on the inorganic particles at the boiling point of liquid nitrogen (-196°C).

[0131] The sample used for SEM observation or BET specific surface area measurement is an inorganic particle used as a material for forming the insulating layer, or an inorganic particle taken out from the insulating layer. There is no limitation on the method for taking out the inorganic particles from the insulating layer, and for example, the following methods can be cited: a method of heating the insulating layer to about 800° C. to make the binder resin disappear and take out the inorganic particles; a method of immersing the insulating layer in an organic solvent to dissolve the binder resin using the organic solvent and take out the inorganic particles, etc.

[0132] From the perspective of improving the electrical insulation of the insulating layer, and increasing the porosity of the insulating layer to improve ion permeability and improve the discharge characteristics of the battery, the mass proportion of the inorganic particles in the insulating layer of the first method is 50 mass% or more, preferably 55 mass% or more, and more preferably 65 mass% or more.

[0133] From the perspective of improving the adhesion between the insulating layer and the electrode and increasing the coulombic efficiency and cell strength of the battery, the mass ratio of the inorganic particles in the insulating layer of the first embodiment is less than 90 mass %, preferably less than 88 mass %, and more preferably less than 85 mass %.

[0134] -First Type of Organic Filler-

[0135] As organic fillers, for example, particles formed from cross-linked polymers such as cross-linked poly(meth)acrylic acid, cross-linked poly(meth)acrylate, cross-linked polysiloxane, cross-linked polystyrene, cross-linked polydivinylbenzene, styrene-divinylbenzene copolymer cross-linked products, melamine resins, phenolic resins, benzoguanamine-formaldehyde condensates, etc.; particles formed from heat-resistant polymers such as polysulfone, polyacrylonitrile, aromatic polyamide, polyacetal, etc.; and the like. These organic fillers can be used alone or in combination of two or more. In the present disclosure, the expression "(meth)acrylic-" means that it can be either "acrylic-" or "methacrylic-".

[0136] -Other ingredients of the first method-

[0137] The insulating layer may contain additives such as a dispersant such as a surfactant, a wetting agent, a defoaming agent, and a pH adjuster, etc. These may be added to the coating liquid for forming the insulating layer.

[0138] [Characteristics of the Insulating Layer of the First Embodiment]

[0139] The thickness of the insulating layer is preferably 5.0 μm or more, more preferably 6.0 μm or more, and further preferably 7.0 μm or more from the viewpoint of electrical insulation and mechanical strength of the insulating layer. From the viewpoint of ion permeability and battery energy density, it is preferably 30 μm or less, more preferably 25 μm or less, and further preferably 20 μm or less.

[0140] The mass per unit area of ​​the insulating layer is preferably 4 g / m from the viewpoint of the electrical insulation and mechanical strength of the insulating layer. 2 More preferably 5g / m 2 More preferably, 9 g / m 2 From the viewpoint of ion permeability and battery energy density, it is preferably less than 40 g / m 2 , more preferably less than 35g / m 2 , more preferably less than 30g / m 2 .

[0141] The porosity of the insulating layer is preferably 40% or more, more preferably 42% or more, and further preferably 46% or more from the viewpoint of ion permeability, and is preferably less than 80%, more preferably less than 75%, and further preferably less than 65% from the viewpoint of electrical insulation and mechanical strength of the insulating layer.

[0142] The porosity ε (%) of the insulating layer was determined by the following method.

[0143] The mass per unit area of ​​the insulating layer is divided by the thickness of the insulating layer to obtain the bulk density d1 of the insulating layer. The true density d0 of the insulating layer is calculated by the following formula (1). Then, the porosity ε (%) of the insulating layer is calculated by the following formula (2).

[0144] Formula (1) d0 = 100 / (resin solid content ratio of insulating layer / resin density+inorganic particle solid content ratio of insulating layer / inorganic particle density)

[0145] Formula (2) ···ε=(1-d1 / d0)×100

[0146] [Electrolyte of the First Embodiment]

[0147] Examples of the electrolyte solution include a solution obtained by dissolving a lithium salt in a non-aqueous solvent.

[0148] Examples of lithium salts include LiPF6, LiBF4, and LiClO4.

[0149] Examples of the non-aqueous solvent include cyclic carbonates such as ethylene carbonate, propylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, and vinylene carbonate; chain carbonates such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and fluorinated products thereof; cyclic esters such as γ-butyrolactone and γ-valerolactone; etc. These may be used alone or in combination.

[0150] As the electrolyte of the lithium ion secondary battery, a solution prepared by mixing cyclic carbonate and chain carbonate at a mass ratio of cyclic carbonate:chain carbonate=20:80 to 40:60 and dissolving lithium salt in a range of 0.5 mol / L to 1.5 mol / L is suitable.

[0151] <<Non-aqueous secondary battery of the second embodiment>>

[0152] The non-aqueous secondary battery of the second mode has a positive electrode, a negative electrode, an insulating layer, and an electrolyte. The insulating layer is a single layer with one side connected to the positive electrode and the other side connected to the negative electrode. The insulating layer contains a polyvinylidene fluoride resin and inorganic particles, and the polymerization component of the polyvinylidene fluoride resin contains vinylidene fluoride and a monomer represented by the following general formula (1). Hereinafter, the polyvinylidene fluoride resin containing vinylidene fluoride and a monomer represented by the following general formula (1) in the polymerization component is referred to as "PVDF resin (1)".

[0153] [Chemical formula 2]

[0154]

[0155] In the general formula (1), R 1 , R 2 and R3 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 5 carbon atoms, a carboxyl group, or a derivative of a carboxyl group, X represents a single bond, an alkylene group having 1 to 5 carbon atoms, or an alkylene group having 1 to 5 carbon atoms having a substituent, and Y represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkyl group having 1 to 5 carbon atoms substituted with at least one hydroxyl group, an alkyl group having 1 to 5 carbon atoms substituted with at least one carboxyl group, or -ROC(=O)-(CH2) n -C(=O)-OH (R represents an alkylene group having 1 to 5 carbon atoms, and n represents an integer greater than 0).

[0156] Hereinafter, the “positive electrode” and the “negative electrode” are collectively referred to as an “electrode.” In addition, the “non-aqueous secondary battery of the second embodiment” is also simply referred to as a “battery.”

[0157] In the battery of the second method, the insulating layer is a single layer. Therefore, (1) there is no boundary between layers inside the insulating layer, so the discharge characteristics and coulombic efficiency of the battery can be improved, and (2) interlayer delamination will not occur inside the insulating layer, so the resistance of the insulating layer can be suppressed to a low level, which can improve the coulombic efficiency and battery cell strength of the battery.

[0158] In the battery of the second mode, the insulating layer includes a PVDF resin (1). When a polyvinylidene fluoride resin, a styrene-butadiene copolymer, etc. are used as a binder resin for the electrode active material layer, the PVDF resin (1) is a polyvinylidene fluoride resin, thereby showing affinity for the polyvinylidene fluoride resin of the electrode active material layer, and by having a portion from a monomer represented by the general formula (1), the styrene-butadiene copolymer of the electrode active material layer shows affinity. The insulating layer containing the resin having high affinity for the binder resin of the electrode active material layer is well bonded to the electrode, thereby improving the coulombic efficiency and battery cell strength of the battery.

[0159] Furthermore, when the stack of electrodes and insulating layers is hot-pressed during the manufacture of a battery, the insulating layer containing the resin having high affinity for the binder resin of the electrode active material layer can be well bonded to the electrode even when the hot-pressing is performed under relatively mild conditions of temperature and pressure. Therefore, the insulating layer containing the resin having high affinity for the binder resin of the electrode active material layer will not clog the pores of the insulating layer during the manufacture of the battery, and the ion permeability can be maintained, thereby improving the discharge characteristics of the battery.

[0160] The above-mentioned respective structures work together to provide a complementary effect, so that the non-aqueous secondary battery of the second embodiment is excellent in discharge characteristics, coulombic efficiency, and cell strength, and therefore has high reliability.

[0161] Hereinafter, the configuration of the nonaqueous secondary battery of the second embodiment will be described in detail.

[0162] [Positive Electrode of the Second Embodiment]

[0163] The positive electrode of the second embodiment has the same meaning as the positive electrode of the first embodiment. The matters described in the "positive electrode of the first embodiment" can be applied to the positive electrode of the second embodiment.

[0164] [Negative Electrode of the Second Embodiment]

[0165] The negative electrode of the second embodiment has the same meaning as the negative electrode of the first embodiment. The matters described in the "negative electrode of the first embodiment" can be applied to the negative electrode of the second embodiment.

[0166] [Insulating layer of the second embodiment]

[0167] The insulating layer of the second aspect has the same meaning as the insulating layer of the first aspect, and the same also applies to one example of the embodiment.

[0168] The insulating layer of the second embodiment contains a PVDF-based resin (1) and inorganic particles. The insulating layer may contain other resins other than the PVDF-based resin (1), an organic filler, and the like.

[0169] -PVDF resin (1)-

[0170] The insulating layer of the second embodiment contains a PVDF-based resin (1). The PVDF-based resin (1) contains at least vinylidene fluoride (also referred to as VDF) and a monomer represented by the following general formula (1) as polymerizable components.

[0171] [Chemical formula 3]

[0172]

[0173] In the general formula (1), R 1 , R 2 and R 3 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 5 carbon atoms, a carboxyl group, or a derivative of a carboxyl group, X represents a single bond, an alkylene group having 1 to 5 carbon atoms, or an alkylene group having 1 to 5 carbon atoms having a substituent, and Y represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkyl group having 1 to 5 carbon atoms substituted with at least one hydroxyl group, an alkyl group having 1 to 5 carbon atoms substituted with at least one carboxyl group, or -ROC(=O)-(CH2) n -C(=O)-OH (R represents an alkylene group having 1 to 5 carbon atoms, and n represents an integer greater than 0).

[0174] In the general formula (1), R 1 , R 2 and R 3 The halogen atom represented by may be any of a fluorine atom, a chlorine atom, a bromine atom and an iodine atom, and is preferably a fluorine atom.

[0175] In the general formula (1), R 1 , R 2 and R 3 The alkyl group having 1 to 5 carbon atoms represented by R includes, for example, methyl, ethyl, n-propyl, n-butyl, and n-pentyl as straight-chain alkyl groups; and isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, neopentyl, and tert-pentyl as branched-chain alkyl groups. 1 , R 2 and R 3 The alkyl group having 1 to 5 carbon atoms in the group is preferably an alkyl group having 1 to 4 carbon atoms, and more preferably an alkyl group having 1 to 3 carbon atoms.

[0176] In the general formula (1), R 1 , R 2 and R 3 Examples of the derivatives of the carboxyl group represented by include -C(=O)-OR 4 (R 4 represents an alkyl group. ) as R 4 For example, the linear alkyl group may be methyl, ethyl, n-propyl, n-butyl, and n-pentyl; the branched alkyl group may be isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, neopentyl, and tert-pentyl. 4 , preferably an alkyl group having 1 to 5 carbon atoms, more preferably an alkyl group having 1 to 4 carbon atoms, and further preferably an alkyl group having 1 to 3 carbon atoms.

[0177] In the general formula (1), the alkylene group having 1 to 5 carbon atoms represented by X includes, for example, methylene, ethylene, n-propylene, n-butylene, and n-pentylene as linear alkylene groups; and isopropylene, isobutylene, sec-butylene, tert-butylene, isopentylene, neopentylene, and tert-pentylene as branched alkylene groups. The alkylene group having 1 to 5 carbon atoms in X is preferably an alkylene group having 1 to 4 carbon atoms, and more preferably an alkylene group having 1 to 3 carbon atoms.

[0178] In the general formula (1), as the substituent in the alkylene group having 1 to 5 carbon atoms represented by X and having a substituent, for example, a halogen atom may be mentioned, and it may be any atom selected from the group consisting of a fluorine atom, a chlorine atom, a bromine atom and an iodine atom. As the substituted alkylene group having 1 to 5 carbon atoms in X, for example, a methylene group, an ethylene group, an n-propylene group, an n-butylene group and an n-pentylene group may be mentioned as a straight-chain alkylene group; and an isopropylene group, an isobutylene group, a sec-butylene group, a tert-butylene group, an isopentylene group, a neopentylene group and a tert-pentylene group may be mentioned as a branched alkylene group. As the substituted alkylene group having 1 to 5 carbon atoms in X, an alkylene group having 1 to 4 carbon atoms is preferred, and an alkylene group having 1 to 3 carbon atoms is more preferred.

[0179] In the general formula (1), the alkyl group having 1 to 5 carbon atoms represented by Y includes, for example, methyl, ethyl, n-propyl, n-butyl, and n-pentyl as linear alkyl groups; and isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, neopentyl, and tert-pentyl as branched alkyl groups. The alkyl group having 1 to 5 carbon atoms in Y is preferably an alkyl group having 1 to 4 carbon atoms, and more preferably an alkyl group having 1 to 3 carbon atoms.

[0180] In the general formula (1), the alkyl group having 1 to 5 carbon atoms substituted by at least one hydroxyl group represented by Y may be, for example, a methyl group, an ethyl group, an n-propyl group, an n-butyl group, and an n-pentyl group as a straight-chain alkyl group; and an isopropyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an isopentyl group, a neopentyl group, and a tert-pentyl group as a branched alkyl group. The alkyl group having 1 to 5 carbon atoms substituted by Y is preferably an alkyl group having 1 to 4 carbon atoms, and more preferably an alkyl group having 1 to 3 carbon atoms. The number of substitutions of the hydroxyl group is preferably 1 or 2, and more preferably 1.

[0181] In the general formula (1), examples of the alkyl group having 1 to 5 carbon atoms and substituted with at least one hydroxy group represented by Y include 2-hydroxyethyl, 2-hydroxypropyl and 4-hydroxybutyl.

[0182] In the general formula (1), the alkyl group having 1 to 5 carbon atoms substituted by at least one carboxyl group represented by Y may be, for example, a methyl group, an ethyl group, an n-propyl group, an n-butyl group, and an n-pentyl group as a straight-chain alkyl group; and an isopropyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an isopentyl group, a neopentyl group, and a tert-pentyl group as a branched alkyl group. The alkyl group having 1 to 5 carbon atoms substituted by Y is preferably an alkyl group having 1 to 4 carbon atoms, and more preferably an alkyl group having 1 to 3 carbon atoms. The number of substitutions of the carboxyl group is preferably 1 or 2, and more preferably 1.

[0183] In the general formula (1), examples of the alkyl group having 1 to 5 carbon atoms substituted with at least one carboxyl group represented by Y include 2-carboxyethyl, 2-carboxypropyl and 4-carboxybutyl.

[0184] In the general formula (1), Y represents -ROC(=O)-(CH2) n In -C(=O)-OH, R represents an alkylene group having 1 to 5 carbon atoms, and n represents an integer of 0 or greater.

[0185] Examples of R include methylene, ethylene, n-propylene, n-butylene, and n-pentylene as linear alkylene groups, and isopropylene, isobutylene, sec-butylene, tert-butylene, isopentylene, neopentylene, and tert-pentylene as branched alkylene groups. R is preferably an alkylene group having 1 to 4 carbon atoms, and more preferably an alkylene group having 1 to 3 carbon atoms.

[0186] n is preferably an integer of 0 to 5, more preferably an integer of 1 to 4, and even more preferably 2 or 3.

[0187] Specific examples of the group include -(CH2)2-OC(=O)-(CH2)2-C(=O)-OH.

[0188] Examples of the monomer represented by the general formula (1) include the following monomers: 1 , R 2 and R 3 A monomer in which each is independently a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, X is a single bond, and Y is an alkyl group having 1 to 4 carbon atoms or an alkyl group having 1 to 3 carbon atoms substituted with at least one hydroxyl group.

[0189] Examples of the monomer represented by the general formula (1) include acrylic monomers, unsaturated dibasic acids, and monoesters of unsaturated dibasic acids.

[0190] Examples of acrylic monomers include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-carboxyethyl (meth)acrylate, 2-carboxypropyl (meth)acrylate, 4-carboxybutyl (meth)acrylate, butenoic acid, pentenoic acid, hexenoic acid, (meth)acryloyloxyethylsuccinic acid, etc. In the present disclosure, the expression "(meth)acrylic-" means that it can be either "acrylic-" or "methacrylic-".

[0191] Examples of the unsaturated dibasic acid include unsaturated dicarboxylic acids, and more specifically, maleic acid, maleic anhydride, citraconic acid, itaconic acid, and the like.

[0192] Examples of the monoester of the unsaturated dibasic acid include monomethyl maleate, monoethyl maleate, monomethyl citraconic acid, monoethyl citraconic acid, monomethyl itaconate, and monoethyl itaconate. Among them, monomethyl maleate and monomethyl citraconic acid are preferred.

[0193] In the PVDF-based resin (1), from the viewpoint of affinity for the resin contained in the electrode active material layer, the proportion of the monomer represented by the general formula (1) in all polymer components is preferably 0.1 mol % or more, more preferably 0.2 mol % or more, and further preferably 0.5 mol % or more.

[0194] In the PVDF resin (1), the proportion of the monomer represented by the general formula (1) in all polymer components is preferably 5.0 mol% or less, more preferably 4.0 mol% or less, and even more preferably 3.0 mol% or less, from the viewpoint of low influence on the electrode active material.

[0195] The PVDF resin (1) may contain other monomers in addition to VDF and the monomer represented by the general formula (1) in the polymerized components. Examples of other monomers include halogen-containing monomers such as hexafluoropropylene, tetrafluoroethylene, trifluoroethylene, chlorotrifluoroethylene, vinyl fluoride, and trichloroethylene.

[0196] The PVDF resin (1) is preferably a resin containing hexafluoropropylene (also referred to as HFP) in the polymer components. By increasing or decreasing the proportion of HFP in the total polymer components, the crystallinity of the resin, the adhesion to the electrode active material layer, the solubility resistance to the electrolyte, etc. can be controlled within a suitable range.

[0197] In the PVDF-based resin (1), the proportion of HFP in all polymer components is preferably greater than 2.0 mol%, more preferably greater than 3.5 mol%, further preferably 4.0 mol% or more, further preferably 4.5 mol% or more, preferably 7.0 mol% or less, more preferably 6.5 mol% or less, further preferably 6.0 mol% or less.

[0198] In the PVDF-based resin (1), the proportion of VDF in all polymer components is preferably 70 mol% or more, more preferably 80 mol% or more, further preferably 90 mol% or more, and preferably 99 mol% or less, more preferably 98 mol% or less.

[0199] The PVDF-based resin (1) is preferably a ternary copolymer composed of VDF, HFP, and a monomer represented by the general formula (1). In the ternary copolymer, the proportion of the monomer represented by the general formula (1) in all polymer components is preferably 0.1 mol% or more, more preferably 0.2 mol% or more, and even more preferably 0.3 mol% or more, and is preferably 5.0 mol% or less, more preferably 4.0 mol% or less, and even more preferably 2.0 mol% or less, and the proportion of HFP in all polymer components is preferably greater than 2.0 mol%, more preferably greater than 2.1 mol%, even more preferably 2.2 mol% or more, even more preferably 2.3 mol% or more, and is preferably 7.0 mol% or less, more preferably 6.5 mol% or less, and even more preferably 6.0 mol% or less.

[0200] The terpolymer formed of VDF, HFP, and the monomer represented by the general formula (1) is preferably a VDF-HFP-acrylic acid terpolymer. In the acrylic acid terpolymer, the proportion of acrylic acid in all polymer components is preferably 0.1 mol% or more, more preferably 0.2 mol% or more, and even more preferably 0.3 mol% or more, and preferably 5.0 mol% or less, more preferably 4.0 mol% or less, and even more preferably 2.0 mol% or less, and the proportion of HFP in all polymer components is preferably greater than 2.0 mol%, more preferably greater than 2.1 mol%, even more preferably 2.2 mol% or more, even more preferably 2.3 mol% or more, and preferably 7.0 mol% or less, more preferably 6.5 mol% or less, and even more preferably 6.0 mol% or less.

[0201] The weight average molecular weight (Mw) of the PVDF resin (1) is preferably 300,000 or more, more preferably 500,000 or more, and even more preferably 1,000,000 or more, from the viewpoint of preventing clogging of pores in the insulating layer when heat is applied to the insulating layer during battery production.

[0202] From the viewpoint that the resin moderately softens when heat is applied to the insulating layer during battery manufacturing and the insulating layer and the electrode are well bonded, the weight average molecular weight (Mw) of the PVDF-based resin (1) is preferably 3 million or less, more preferably 2.5 million or less, and even more preferably 2.3 million or less.

[0203] The mass ratio of the PVDF-based resin (1) in the second embodiment in the insulating layer is preferably 10 to 50 mass%, more preferably 15 to 50 mass%, and even more preferably 20 to 50 mass%.

[0204] The content of the PVDF-based resin (1) contained in the insulating layer of the second embodiment is preferably 85 to 100% by mass, more preferably 90 to 100% by mass, and even more preferably 95 to 100% by mass, based on the total amount of all resins contained in the insulating layer.

[0205] -Other resins in the second embodiment-

[0206] The insulating layer of the second embodiment may contain other resins in addition to the PVDF-based resin (1). As other resins of the second embodiment, the resins listed in "other resins of the first embodiment" can be applied, and the preferred content in the insulating layer is the same.

[0207] -Inorganic particles of the second embodiment-

[0208] The inorganic particles of the second embodiment are synonymous with the inorganic particles of the first embodiment. The matters described in "the inorganic particles of the first embodiment" are applicable to the inorganic particles of the second embodiment. It should be noted that in the second embodiment, the following content applies to the mass ratio of the inorganic particles in the insulating layer.

[0209] From the perspective of improving the electrical insulation of the insulating layer, and from the perspective of increasing the porosity of the insulating layer to improve ion permeability and improve the discharge characteristics of the battery, the mass proportion of the inorganic particles in the second mode in the insulating layer is preferably 50 mass % or more, more preferably 55 mass % or more, and more preferably 65 mass % or more.

[0210] From the viewpoint of improving the mechanical strength of the insulating layer, improving the adhesion between the insulating layer and the electrode, and improving the coulombic efficiency and battery cell strength of the battery, the mass proportion of the inorganic particles in the insulating layer of the second method is preferably less than 90 mass%, more preferably less than 88 mass%, and further preferably less than 85 mass%.

[0211] - Second Form of Organic Filler -

[0212] The organic filler of the second embodiment has the same meaning as the organic filler of the first embodiment. The matters described in the "organic filler of the first embodiment" can be applied to the organic filler of the second embodiment.

[0213] -Other ingredients of the second method-

[0214] The other components of the second embodiment have the same meanings as those of the first embodiment.

[0215] [Characteristics of the Insulating Layer of the Second Embodiment]

[0216] The characteristics of the insulating layer of the second embodiment are the same as those described in “Characteristics of the insulating layer of the first embodiment”.

[0217] [Electrolyte of the Second Embodiment]

[0218] The electrolyte solution of the second embodiment has the same meaning as the electrolyte solution of the first embodiment. The matters described in the "electrolyte solution of the first embodiment" can be applied to the electrolyte solution of the second embodiment.

[0219] <<Non-aqueous secondary battery of the third embodiment>>

[0220] The non-aqueous secondary battery of the third embodiment comprises a positive electrode, a negative electrode, an insulating layer, and an electrolyte. The insulating layer is a single layer having one side in contact with the positive electrode and the other side in contact with the negative electrode, and contains a resin and inorganic particles, and has a thickness of 5 μm to 30 μm. Furthermore, the inorganic particles of the insulating layer include metal sulfate particles.

[0221] Hereinafter, the “positive electrode” and the “negative electrode” are collectively referred to as an “electrode.” In addition, the “non-aqueous secondary battery of the third embodiment” is also simply referred to as a “battery.”

[0222] In the battery of the third embodiment, the insulating layer is a single layer. Therefore, (1) there is no boundary between layers inside the insulating layer, so the discharge characteristics and discharge capacity retention of the battery can be improved, and (2) the resistance of the insulating layer can be suppressed to a low level and the occurrence of micro short circuits can be suppressed. In addition, the battery cell strength can be improved.

[0223] In the battery of the third embodiment, the thickness of the insulating layer is 5 μm or more from the viewpoint of electrical insulation and mechanical strength of the insulating layer, and is 30 μm or less from the viewpoint of improving ion permeability and thus improving discharge characteristics of the battery.

[0224] In the battery of the third embodiment, the inorganic particles of the insulating layer include metal sulfate particles. The metal sulfate particles are stable to the electrolyte and are not easy to generate gas. Therefore, compared with a battery having an insulating layer in which all inorganic particles are inorganic particles other than metal sulfate particles, a battery having an insulating layer in which part or all of the inorganic particles are metal sulfate particles is superior in at least one of discharge characteristics, discharge capacity retention at high temperature, and difficulty in generating micro short circuits.

[0225] The above-mentioned structures work together to enhance each other, so that the non-aqueous secondary battery of the third embodiment has high reliability.

[0226] Hereinafter, the configuration of the nonaqueous secondary battery of the third embodiment will be described in detail.

[0227] [Third-party positive electrode]

[0228] The positive electrode of the third embodiment has the same meaning as the positive electrode of the first embodiment. The matters described in the "positive electrode of the first embodiment" can be applied to the positive electrode of the third embodiment.

[0229] [Third-party negative electrode]

[0230] The negative electrode of the third embodiment has the same meaning as the negative electrode of the first embodiment. The matters described in the "negative electrode of the first embodiment" can be applied to the negative electrode of the third embodiment.

[0231] [Third-party insulation layer]

[0232] The insulating layer of the third aspect has the same meaning as the insulating layer of the first aspect, and the same also applies to the example of the embodiment.

[0233] The insulating layer of the third embodiment contains a resin and inorganic particles, and part or all of the inorganic particles are metal sulfate particles. The insulating layer may contain inorganic particles other than metal sulfate particles, organic fillers, and the like.

[0234] - Third-party resin -

[0235] The resin contained in the insulating layer of the third embodiment is preferably a resin that is stable in the electrolyte, electrochemically stable, has a function of connecting inorganic particles, and can adhere to the electrode. The insulating layer may contain only one resin or two or more resins.

[0236] The type of resin contained in the insulating layer of the third embodiment is not limited. As the resin, for example, polyvinylidene fluoride resin, acrylic resin, fluorine rubber, styrene-butadiene copolymer, homopolymer or copolymer of vinyl nitrile compound (acrylonitrile, methacrylonitrile, etc.), carboxymethyl cellulose, hydroxyalkyl cellulose, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, polyether (polyethylene oxide, polypropylene oxide, etc.), polyamide, fully aromatic polyamide (also called aromatic polyamide), polyimide, polyamide-imide, polysulfone, polyketone, polyether ketone, polyether sulfone, polyether imide, and mixtures thereof can be cited.

[0237] As the resin of the third embodiment, from the viewpoint of the adhesion of the insulating layer to the electrode, a polyvinylidene fluoride resin is preferably used. As the polyvinylidene fluoride resin, for example, homopolymers of vinylidene fluoride (i.e., polyvinylidene fluoride); copolymers of vinylidene fluoride and halogen-containing monomers such as hexafluoropropylene, tetrafluoroethylene, trifluoroethylene, chlorotrifluoroethylene, vinyl fluoride, and trichloroethylene; and mixtures thereof. The polyvinylidene fluoride resin may be used alone or in combination of two or more.

[0238] As polyvinylidene fluoride resin, from the viewpoint of the adhesion of the insulating layer to the electrode, preferably a copolymer of vinylidene fluoride (VDF) and hexafluoropropylene (HFP) (VDF-HFP copolymer). In the present disclosure, VDF-HFP copolymer includes a copolymer obtained by polymerizing only VDF and HFP (referred to as a VDF-HFP binary copolymer.), and any copolymer obtained by polymerizing VDF and HFP with other monomers. As other monomers herein, for example, halogen-containing monomers such as tetrafluoroethylene, trifluoroethylene, trifluorochloroethylene, vinyl fluoride, and trichloroethylene can be cited.

[0239] By increasing or decreasing the content of the HFP unit in the VDF-HFP copolymer, the crystallinity, adhesion to the electrode active material layer, and dissolution resistance to the electrolyte solution of the copolymer can be controlled within an appropriate range.

[0240] In the VDF-HFP copolymer, the proportion of HFP in all polymer components is preferably greater than 1.0 mol%, more preferably greater than 1.5 mol%, further preferably 2.0 mol% or more, further preferably 2.2 mol% or more, preferably 7.0 mol% or less, more preferably 6.5 mol% or less, further preferably 6.0 mol% or less.

[0241] The weight average molecular weight (Mw) of the polyvinylidene fluoride-based resin contained in the insulating layer of the third embodiment is preferably 900,000 or more and 1,500,000 or less.

[0242] If the Mw of the polyvinylidene fluoride resin is 900,000 or more, the electrical insulation of the insulating layer is good, and when heat is applied to the insulating layer during battery manufacturing, clogging of the pores of the insulating layer is not likely to occur. From this viewpoint, the Mw of the polyvinylidene fluoride resin is preferably 900,000 or more, more preferably 1,000,000 or more, and further preferably 1,100,000 or more.

[0243] If the Mw of the polyvinylidene fluoride resin is 1.5 million or less, when heat is applied to the insulating layer during battery manufacturing, the insulating layer and the electrode are well bonded, and it is not easy to generate a gap between the insulating layer and the electrode. From this viewpoint, the Mw of the polyvinylidene fluoride resin is preferably 1.5 million or less, more preferably 1.4 million or less, and further preferably 1.3 million or less.

[0244] The mass ratio of the polyvinylidene fluoride-based resin in the third embodiment in the insulating layer is preferably 10% by mass to 50% by mass, more preferably 15% by mass to 50% by mass, and even more preferably 20% by mass to 50% by mass.

[0245] The content of the polyvinylidene fluoride-based resin contained in the insulating layer of the third embodiment is preferably 85 to 100 mass %, more preferably 90 to 100 mass %, and even more preferably 95 to 100 mass %, based on the total amount of all resins contained in the insulating layer.

[0246] The content of the resin other than the polyvinylidene fluoride resin contained in the insulating layer of the third embodiment is preferably 0 to 15% by mass, more preferably 0 to 10% by mass, and even more preferably 0 to 5% by mass, based on the total amount of all resins contained in the insulating layer.

[0247] -Third Form Inorganic Particles-

[0248] The particle shape of the inorganic particles of the third embodiment is not limited, and can be any of spherical, plate-like, needle-like, and irregular shapes. From the perspective of suppressing battery short circuits or being easily densely filled in the insulating layer, the inorganic particles are preferably spherical or plate-like particles.

[0249] At least a portion of the inorganic particles of the third embodiment are metal sulfate particles. The inorganic particles may also include other inorganic particles other than the metal sulfate particles. As other inorganic particles other than the metal sulfate particles, for example, metal hydroxide particles, metal oxide particles, metal carbonate particles, metal nitride particles, metal fluoride particles, particles of clay minerals, etc. may be cited. The inorganic particles may be used alone or in combination of two or more kinds of different materials.

[0250] The metal sulfate particles, metal hydroxide particles, metal oxide particles, metal carbonate particles, metal nitride particles, metal fluoride particles, and clay mineral particles of the third embodiment are respectively synonymous with the metal sulfate particles, metal hydroxide particles, metal oxide particles, metal carbonate particles, metal nitride particles, metal fluoride particles, and clay mineral particles in the "inorganic particles of the first embodiment", and the preferred embodiments are the same.

[0251] The content of the metal sulfate particles contained in the insulating layer of the third embodiment is preferably 85 to 100 mass %, more preferably 90 to 100 mass %, and further preferably 95 to 100 mass % relative to the total amount of all inorganic particles contained in the insulating layer.

[0252] The content of inorganic particles other than the metal sulfate particles contained in the insulating layer of the third embodiment is preferably 0 to 15% by mass, more preferably 0 to 10% by mass, and even more preferably 0 to 5% by mass, based on the total amount of all inorganic particles contained in the insulating layer.

[0253] From the viewpoint of making the insulating layer porous and improving ion permeability, the average primary particle size of the metal sulfate particles contained in the insulating layer of the third embodiment is preferably 0.01 μm or more, more preferably 0.02 μm or more, and even more preferably 0.03 μm or more.

[0254] From the perspective of thinning the insulating layer to increase the energy density of the battery, and from the perspective of increasing the filling degree of the metal sulfate particles in the insulating layer to increase the strength of the insulating layer, the average primary particle size of the metal sulfate particles contained in the insulating layer of the third form is preferably less than 1.00 μm, more preferably less than 0.50 μm, and further preferably less than 0.30 μm.

[0255] The method for determining the average primary particle size of the inorganic particles of the third embodiment is the same as the method for determining the average primary particle size of the inorganic particles of the first embodiment.

[0256] From the perspective of improving the electrical insulation of the insulating layer, and from the perspective of increasing the porosity of the insulating layer to improve ion permeability and improve the discharge characteristics of the battery, the mass proportion of the inorganic particles of the third formula in the insulating layer is preferably 50 mass % or more, more preferably 55 mass % or more, and further preferably 60 mass % or more.

[0257] From the perspective of ensuring good adhesion between the insulating layer and the electrode and improving the coulombic efficiency and cell strength of the battery, the mass proportion of the inorganic particles of the third formula in the insulating layer is preferably less than 90 mass %, more preferably less than 88 mass %, and further preferably less than 85 mass %.

[0258] -Third-party organic filler-

[0259] The organic filler of the third embodiment has the same meaning as the organic filler of the first embodiment. The matters described in the "organic filler of the first embodiment" can be applied to the organic filler of the third embodiment.

[0260] -Other ingredients of the third method-

[0261] The other components of the third embodiment have the same meanings as those of the first embodiment.

[0262] [Characteristics of the insulation layer of the third method]

[0263] The characteristics of the insulating layer of the third embodiment are the same as those described in “the characteristics of the insulating layer of the first embodiment”.

[0264] [Third-party electrolyte]

[0265] The electrolyte solution of the third embodiment has the same meaning as the electrolyte solution of the first embodiment. The matters described in the "electrolyte solution of the first embodiment" can be applied to the electrolyte solution of the third embodiment.

[0266] Figure 1 This is an example of an embodiment of the non-aqueous secondary battery of the present disclosure. Figure 1 A diagram schematically showing a cross section of a battery. Figure 1 This is an example of an embodiment of a non-aqueous secondary battery and does not limit the embodiment.

[0267] Figure 1 The non-aqueous secondary battery 100 shown includes a battery element 10, an electrolyte solution 50, and an outer packaging material 90. The battery element 10 and the electrolyte solution 50 are accommodated inside the outer packaging material 90.

[0268] The battery element 10 includes a positive electrode 20, an insulating layer 30, and a negative electrode 40. The battery element 10 has a structure in which at least one layer of the positive electrode 20, the insulating layer 30, and the negative electrode 40 are stacked in this order.

[0269] The positive electrode 20 includes a positive electrode collector 22 and positive electrode active material layers 24 disposed on both surfaces of the positive electrode collector 22. One end of the positive electrode collector 22 is not provided with the positive electrode active material layer 24 and has, for example, a tab shape.

[0270] The negative electrode 40 includes a negative electrode collector 42 and negative electrode active material layers 44 disposed on both surfaces of the negative electrode collector 42. One end of the negative electrode collector 42 is not provided with the negative electrode active material layer 44 and has, for example, a tab shape.

[0271] One surface of the insulating layer 30 is in contact with the positive electrode active material layer 24, and the other surface is in contact with the negative electrode active material layer 44. The insulating layer 30 is a porous layer, and the insulating layer 30 is impregnated with an electrolyte solution 50.

[0272] Examples of the outer packaging material 90 include metal cases and aluminum laminated film packages.

[0273] The non-aqueous secondary battery 100 has a positive terminal (not shown) and a negative terminal (not shown) outside the outer packaging material 90. A plurality of positive electrode collectors 22 are connected to the positive terminal, and a plurality of negative electrode collectors 42 are connected to the negative terminal. A tab may be interposed between the positive terminal and the positive electrode collector 22 (or between the negative terminal and the negative electrode collector 42).

[0274] Examples of the shape of the nonaqueous secondary battery 100 include a square shape, a cylindrical shape, and a button shape.

[0275] [Method for producing non-aqueous secondary battery]

[0276] The non-aqueous secondary battery of the present disclosure can be manufactured, for example, by the following manufacturing method. That is, the manufacturing method includes the following steps:

[0277] Step A, forming an insulating layer on a support by a wet coating method or a dry coating method;

[0278] Step B, manufacturing a laminate having an insulating layer disposed between a positive electrode and a negative electrode; and

[0279] In step C, the laminate is subjected to wet hot pressing and / or dry hot pressing.

[0280] -Process A-

[0281] The support refers to a sheet-like material on which the coating liquid for forming an insulating layer is applied. Examples of the support include a positive electrode, a negative electrode, and a release sheet.

[0282] The wet coating method refers to a method of solidifying a coating layer in a solidifying liquid, and the dry coating method refers to a method of solidifying a coating layer by drying.

[0283] Examples of implementations of process A include: a process of forming an insulating layer on the active material layer of the positive electrode by wet coating or dry coating; a process of forming an insulating layer on the active material layer of the negative electrode by wet coating or dry coating; and a process of forming an insulating layer on a release sheet by wet coating or dry coating.

[0284] Hereinafter, an embodiment in which an insulating layer is formed on a support by a wet coating method will be described.

[0285] As an embodiment example of the wet coating method, a coating liquid containing a resin and inorganic particles is coated on a support, the support is immersed in a coagulation liquid to solidify the coating layer, and the support is pulled out of the coagulation liquid, washed with water, and dried.

[0286] The coating liquid for forming the insulating layer is prepared by dissolving or dispersing a resin and inorganic particles in a solvent. In the coating liquid, other components other than the resin and the inorganic particles are dissolved or dispersed as necessary.

[0287] The solvent used in the preparation of the coating liquid includes a solvent that dissolves the resin (hereinafter also referred to as a "good solvent"). Examples of the good solvent include polar amide solvents such as N-methylpyrrolidone, dimethylacetamide, and dimethylformamide.

[0288] From the viewpoint of forming an insulating layer with a good porous structure, the solvent used in the preparation of the coating liquid preferably contains a phase separation agent that induces phase separation. Therefore, the solvent used in the preparation of the coating liquid is preferably a mixed solvent of a good solvent and a phase separation agent. The phase separation agent is preferably mixed with the good solvent in an amount that can ensure a range of viscosity suitable for coating. As the phase separation agent, water, methanol, ethanol, propanol, butanol, butanediol, ethylene glycol, propylene glycol, tripropylene glycol, etc. can be cited.

[0289] As the solvent used in the preparation of the coating liquid, from the viewpoint of forming an insulating layer having a good porous structure, the following mixed solvent is preferably used, which is a mixed solvent of a good solvent and a phase separation agent, containing 60% by mass or more of the good solvent and 5% to 40% by mass of the phase separation agent.

[0290] From the viewpoint of forming an insulating layer with a good porous structure, the resin concentration of the coating liquid is preferably 3% to 10% by mass. From the viewpoint of forming an insulating layer with a good porous structure, the inorganic particle concentration of the coating liquid is preferably 2% to 50% by mass.

[0291] The coating liquid may contain a dispersant such as a surfactant, a wetting agent, a defoaming agent, a pH adjuster, etc. These additives may remain in the insulating layer as long as they are electrochemically stable within the use range of the non-aqueous secondary battery and do not inhibit the reaction in the battery.

[0292] Examples of a means for applying the coating liquid to the support include a Mayer bar, a die coater, a reverse roll coater, a roll coater, a gravure coater, and a knife coater.

[0293] The coating layer can be cured by immersing the support body on which the coating layer is formed in a coagulation liquid to cure the resin while inducing phase separation in the coating layer, thereby obtaining a composite body having the insulating layer disposed on the support body.

[0294] The coagulation liquid generally contains a good solvent and a phase separation agent used in the preparation of the coating liquid, and water. From the production point of view, the mixing ratio of the good solvent and the phase separation agent is preferably consistent with the mixing ratio of the mixed solvent used in the preparation of the coating liquid. From the viewpoint of the formation of the porous structure of the insulating layer and the productivity, the water content in the coagulation liquid is preferably 40% to 90% by mass. The temperature of the coagulation liquid is, for example, 20°C to 50°C.

[0295] After the coating layer is solidified in the coagulation liquid, the composite is lifted out of the coagulation liquid and washed with water. The coagulation liquid is removed from the composite by washing with water. Furthermore, water is removed from the composite by drying. The washing is performed, for example, by transporting the composite in a water bath. The drying is performed, for example, by transporting the composite in a high temperature environment, blowing air on the composite, contacting the composite with a hot roller, etc. The drying temperature is preferably 40°C to 80°C. From the viewpoint of removing water from the insulating layer as much as possible so that the water in the insulating layer does not contact the electrolyte, it is preferred to perform reduced pressure drying at a high temperature (for example, 80°C to 110°C).

[0296] The insulating layer can also be formed by a dry coating method. As an embodiment example of the dry coating method, a coating liquid is applied to a support, and the coating layer is dried to volatilize and remove the solvent, thereby forming an insulating layer on the support.

[0297] -Process B-

[0298] As implementation examples of process B, there can be cited: an implementation example in which a positive electrode is overlapped with a negative electrode obtained by forming an insulating layer on a negative electrode active material layer; an implementation example in which a negative electrode is overlapped with a positive electrode obtained by forming an insulating layer on a positive electrode active material layer; an implementation example in which a positive electrode and an insulating layer obtained by peeling off a peeling sheet are overlapped with a negative electrode; and the like.

[0299] The insulating layer may be arranged between the positive electrode and the negative electrode by stacking the positive electrode, the insulating layer and the negative electrode in sequence in at least one layer each (so-called stacking method), or by stacking the positive electrode, the insulating layer, the negative electrode and the insulating layer in sequence and winding them in the length direction.

[0300] -Process C-

[0301] The wet hot pressing refers to performing hot pressing after impregnating the insulating layer with an electrolyte, and the dry hot pressing refers to performing hot pressing without impregnating the coating layer with an electrolyte.

[0302] As an embodiment example of the step C, the following (1) to (3) can be mentioned.

[0303] (1) The stack is placed in an outer packaging material (e.g., an aluminum laminate film package, the same below), an electrolyte is injected therein, and the outer packaging material is made into a vacuum state. The stack is then wet-hot pressed from above the outer packaging material to bond the electrode to the insulating layer and seal the outer packaging material.

[0304] (2) After the laminate is dry-heat-pressed to bond the electrodes and the insulating layer, it is placed in an outer packaging material, an electrolyte is injected therein, and the outer packaging material is sealed after the inner portion is made into a vacuum state.

[0305] (3) After the stack is dry-hot pressed to bond the electrode to the insulating layer, it is placed in an outer packaging material, into which an electrolyte is injected to make the outer packaging material a vacuum state, and then the stack is further wet-hot pressed from above the outer packaging material to bond the electrode to the insulating layer and seal the outer packaging material.

[0306] As the conditions for hot pressing in the production methods (1) to (3) above, for each of dry hot pressing and wet hot pressing, the pressing pressure is preferably 0.1 MPa to 10.0 MPa, and the temperature is preferably 60° C. to 100° C.

[0307] Example

[0308] Hereinafter, the non-aqueous secondary battery of the present disclosure is described in more detail by way of examples. The materials, usage amounts, ratios, processing steps, etc. shown in the following examples may be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the non-aqueous secondary battery of the present disclosure should not be interpreted restrictively based on the specific examples shown below.

[0309] <Measurement method, evaluation method>

[0310] The measuring methods and evaluation methods used in Examples and Comparative Examples are as follows.

[0311] [Thickness of insulation layer]

[0312] The thickness (μm) of the electrode and the thickness (μm) of the composite body having an insulating layer disposed on the electrode were measured at 20 points in a 5 cm × 3 cm rectangle using a contact thickness meter (Mitutoyo Co., Ltd., LITEMATIC VL-50) and averaged to obtain the thickness. The measuring terminal used a cylindrical terminal with a diameter of 5 mm, and during the measurement, the load was adjusted to apply 0.01 N. Then, the value obtained by subtracting the thickness of the electrode from the thickness of the composite body was taken as the thickness (μm) of the insulating layer.

[0313] [Mass per unit area of ​​insulating layer]

[0314] The electrode and the composite body with an insulating layer disposed on the electrode were cut into 5 cm × 3 cm rectangles, and the mass (g) was measured. The mass was divided by the area (0.0015 m 2 ) to find the mass per unit area (g / m 2 Then, the value obtained by subtracting the mass per unit area of ​​the electrode from the mass per unit area of ​​the composite is taken as the mass per unit area of ​​the insulating layer (g / m 2 ).

[0315] [Porosity of insulating layer]

[0316] The porosity ε (%) of the insulating layer was determined by the above-mentioned method.

[0317] [Average primary particle size of inorganic particles]

[0318] The average primary particle size of the inorganic particles is determined by measuring the major diameters of 100 primary particles randomly selected from the inorganic particles before being added to the coating liquid for forming the insulating layer under observation with a scanning electron microscope (SEM) as a sample and averaging the 100 major diameters.

[0319] [Weight average molecular weight of polyvinylidene fluoride resin]

[0320] The weight average molecular weight (Mw) of the polyvinylidene fluoride resin is measured by gel permeation chromatography (GPC). For molecular weight determination based on GPC, a GPC device GPC-900 manufactured by JASCO Corporation is used, two TSKgel SUPER AWM-H manufactured by TOSOH are used as columns, and N,N-dimethylformamide is used as a solvent. The measurement is performed under the conditions of a temperature of 40°C and a flow rate of 0.6 mL / min to obtain a molecular weight converted to polystyrene.

[0321] [Ratio of Monomers Constituting Polyvinylidene Fluoride Resin]

[0322] 10 mg of polyvinylidene fluoride resin was dissolved in 0.6 mL of deuterated dimethyl sulfoxide at 100°C and the reaction mixture was measured at 100°C. 19 F-NMR spectrum, measured at room temperature 1 H-NMR spectrum: The ratio of monomers constituting the polyvinylidene fluoride-based resin was determined from the ratio of the peak intensities derived from the monomers in the NMR spectrum.

[0323] [Discharge characteristics]

[0324] The battery was subjected to five cycles of charge and discharge in the following (a), and then subjected to one cycle of charge and discharge in the following (b).

[0325] (a) 4mA / 4.2V, 15 hours of constant current and constant voltage charging, and 4mA / 2.5V cut-off constant current discharge

[0326] (b) 8mA / 4.2V, 8 hours of constant current and constant voltage charging, and 200mA / 2.5V cut-off constant current discharge

[0327] The discharge capacity of (b) was divided by the discharge capacity of the 5th cycle of (a), and the obtained value was used as the discharge characteristic of the battery. The discharge characteristic of Reference Example 1 was used as a reference value, and the percentage of the discharge characteristics of the embodiment and the comparative example relative to Reference Example 1 was calculated and classified as follows.

[0328] A: More than 95%

[0329] B: 85% or more and less than 95%

[0330] C: 70% or more and less than 85%

[0331] D: less than 70%

[0332] [Coulomb efficiency]

[0333] The discharge capacity of the first cycle of the above (a) was divided by the charge capacity, and the obtained value was taken as the coulombic efficiency of the battery. The coulombic efficiency of Reference Example 1 was taken as a reference value, and the percentages of the coulombic efficiencies of the embodiments and comparative examples relative to Reference Example 1 were calculated and classified as follows.

[0334] A: More than 95%

[0335] B: 85% or more and less than 95%

[0336] C: 70% or more and less than 85%

[0337] D: less than 70%

[0338] [Battery cell strength]

[0339] The battery was subjected to a three-point bending test according to ISO 178 to determine the maximum load (N) that causes the battery to break. The maximum load of Reference Example 1 was used as a reference value, and the percentage of the maximum load of the Examples and Comparative Examples relative to Reference Example 1 was calculated and classified as follows.

[0340] A: More than 90%

[0341] B: Less than 90%

[0342] [Discharge capacity retention rate]

[0343] The battery after the discharge characteristics were evaluated was left in an environment at a temperature of 85° C. for 7 days. Then, after returning to an environment at a temperature of 25° C., one cycle of the charge and discharge in the above-mentioned (a) was performed.

[0344] The discharge capacity after storage at 85°C was divided by the discharge capacity of the fifth cycle of the above (a) before storage, and the obtained value was taken as the discharge capacity retention rate of the battery. The discharge capacity retention rate of Reference Example 1 was used as a reference value, and the percentages of the discharge capacity retention rates of the Examples and Comparative Examples relative to Reference Example 1 were calculated and classified as follows.

[0345] A: More than 95%

[0346] B: less than 95%

[0347] [Minor short circuit]

[0348] 60 batteries were subjected to 5 cycles of charge and discharge in the above-mentioned (a). For each battery, the discharge capacity of each cycle was divided by the charge capacity, and the resulting value (%) was used as the coulombic efficiency. Batteries with a coulombic efficiency of 90% or more in all cycles were judged to be qualified, and batteries that did not meet this were deemed unqualified. The number of qualified batteries in Reference Example 1 was used as a reference value, and the percentages of the number of qualified batteries in the embodiments and comparative examples relative to Reference Example 1 were calculated and classified as follows.

[0349] A: More than 95%

[0350] B: less than 95%

[0351] <<Manufacturing of non-aqueous secondary battery of the first embodiment>>

[0352] [Example 1]

[0353] -Making the positive electrode-

[0354] 94 parts by mass of lithium cobalt oxide powder, 3 parts by mass of acetylene black, 3 parts by mass of polyvinylidene fluoride resin, and an appropriate amount of N-methyl-2-pyrrolidone were kneaded to prepare a slurry. The slurry was coated on an aluminum foil with a thickness of 20 μm, and pressed after drying to obtain a positive electrode (single-sided coating, unit area weight of 20.5 mg / cm 2 , density is 2.95g / cm 3 ).

[0355] - Fabrication of negative electrode -

[0356] 96.2 parts by mass of graphite powder, 2.8 parts by mass of a modified styrene-butadiene copolymer, 1.0 parts by mass of carboxymethyl cellulose, and an appropriate amount of water were kneaded to prepare a slurry. The slurry was coated on a copper foil having a thickness of 15 μm, and after drying, it was pressed to obtain a negative electrode (single-sided coating, unit area weight of 10.0 mg / cm 2 , density is 1.60g / cm 3 ).

[0357] -Insulation layer production-

[0358] A VDF-HFP binary copolymer (weight average molecular weight of 1.13 million, HFP ratio of all polymer components of 2.4 mol%) was dissolved in a mixed solvent of dimethylacetamide (DMAc) and tripropylene glycol (TPG) (DMAc:TPG = 80:20 [mass ratio]) at a concentration of 5 mass%, and then magnesium hydroxide particles (average primary particle size of 0.88 μm) were added and stirred to obtain a coating liquid (1). The mass ratio of the VDF-HFP binary copolymer to the magnesium hydroxide particles (VDF-HFP binary copolymer: magnesium hydroxide particles) was 20:80.

[0359] The coating liquid (1) was applied to the active material layer of the negative electrode using a knife coater. It was immersed in a coagulation liquid (DMAc: water = 50:50 (mass ratio), liquid temperature was 25°C) for 5 minutes to solidify the coating layer, and then washed in a water washing tank at a water temperature of 25°C for 1 minute. It was lifted out of the water washing tank and placed in a constant temperature bath at 70°C, dried for 15 minutes, and then dried under reduced pressure at 110°C for 3 hours. As described above, a composite having a single insulating layer arranged on the negative electrode was obtained.

[0360] -Battery production-

[0361] The positive electrode is cut into 5.0cm×3.0cm, and the composite body with an insulating layer on the negative electrode is cut into 5.2cm×3.2cm, and the pole ears are welded on each. The positive electrode and the composite body are overlapped in such a way that the positive electrode active material layer and the insulating layer are in contact with each other to obtain a laminate. The electrolyte is impregnated into the laminate and sealed in the outer packaging material of the aluminum laminate film. Hot pressing (85°C, 0.5MPa, 2 minutes) is performed from the outer packaging material to bond the electrode and the insulating layer to obtain a battery. As the electrolyte, 1mol / L LiPF6-ethylene carbonate: ethyl methyl carbonate (mass ratio is 3:7) is used. The set capacity of the battery is 40mAh (range of 4.2V-2.5V).

[0362] [Examples 2 to 8, Comparative Examples 1 to 7]

[0363] Each battery was produced in the same manner as in Example 1, except that the material, composition and thickness of the insulating layer were set to the specifications described in Table 1.

[0364] In Examples 7 and 8, magnesium hydroxide particles and barium sulfate particles were used in a ratio of magnesium hydroxide particles to barium sulfate particles of 50:50 (mass ratio).

[0365] [Reference Example 1]

[0366] -Production of a 3-layer diaphragm-

[0367] Using a reverse roll coater, an equal amount of coating liquid (1) was applied to both sides of a polyethylene microporous membrane (thickness 7 μm, porosity 36%, Gurley value 120 seconds / 100 mL). The membrane was immersed in a coagulation liquid (DMAc: water = 50:50 (mass ratio), liquid temperature 40°C) to solidify the coating layer, and then washed in a water washing tank at a water temperature of 40°C and dried. As described above, a separator having a coating layer formed on both sides of the polyethylene microporous membrane was obtained.

[0368] -Battery production-

[0369] The positive electrode and negative electrode of Example 1 were prepared. The positive electrode was cut into 5.0 cm×3.0 cm, and the negative electrode was cut into 5.2 cm×3.2 cm, and electrode tabs were welded to each. The separator was cut into 5.4 cm×3.4 cm.

[0370] The positive electrode, the separator, and the negative electrode are stacked in the order of the positive electrode, the separator, and the negative electrode so that the electrode active material layer is in contact with the separator. The electrolyte (the same electrolyte as that used in Example 1) is impregnated into the stack and sealed in the outer packaging material of the aluminum laminate film. Hot pressing (85°C, 0.5MPa, 2 minutes) is performed from the outer packaging material to bond the electrode and the separator to obtain a battery.

[0371] Table 1 shows the composition, physical properties, and evaluation results of each battery of Examples 1 to 8, Comparative Examples 1 to 7, and Reference Example 1.

[0372] [Table 1]

[0373]

[0374] <<Manufacturing of non-aqueous secondary battery of the second embodiment>> [Example 101]

[0375] -Making the positive electrode-

[0376] 94 parts by mass of lithium cobalt oxide powder, 3 parts by mass of acetylene black, 3 parts by mass of polyvinylidene fluoride resin, and an appropriate amount of N-methyl-2-pyrrolidone were kneaded to prepare a slurry. The slurry was coated on an aluminum foil with a thickness of 20 μm, and pressed after drying to obtain a positive electrode (single-sided coating, unit area weight of 20.5 mg / cm 2 , density is 2.95g / cm 3 ).

[0377] - Fabrication of negative electrode -

[0378] 96.2 parts by mass of graphite powder, 2.8 parts by mass of a modified styrene-butadiene copolymer, 1.0 parts by mass of carboxymethyl cellulose, and an appropriate amount of water were kneaded to prepare a slurry. The slurry was coated on a copper foil having a thickness of 15 μm, and after drying, it was pressed to obtain a negative electrode (single-sided coating, unit area weight of 10.0 mg / cm 2 , density is 1.60g / cm 3 ).

[0379] -Insulation layer production-

[0380] A VDF-HFP-acrylic acid terpolymer in which the ratio of HFP to all polymer components was 2.4 mol% and the ratio of acrylic acid to all polymer components was 0.5 mol% was prepared. This resin is referred to as PVDF-based resin (A).

[0381] The PVDF resin (A) was dissolved in a mixed solvent of dimethylacetamide (DMAc) and tripropylene glycol (TPG) (DMAc:TPG=80:20 [mass ratio]) at a concentration of 5 mass%, and then magnesium hydroxide particles (average primary particle size of 0.88 μm) were added and stirred to obtain a coating liquid (A). The mass ratio of the PVDF resin (A) to the magnesium hydroxide particles (PVDF resin (A): magnesium hydroxide particles) was 20:80.

[0382] Use a knife coater to apply the coating liquid (A) on the active material layer of the negative electrode. Immerse it in a coagulation liquid (DMAc: water = 50:50 (mass ratio), liquid temperature is 25°C) for 5 minutes to solidify the coating layer, and then wash it in a water washing tank with a water temperature of 25°C for 1 minute. Lift it from the water washing tank, put it in a constant temperature bath at 70°C, dry it for 15 minutes, and then dry it under reduced pressure at 110°C for 3 hours. As described above, a composite body with a single insulating layer configured on the negative electrode is obtained.

[0383] -Battery production-

[0384] The positive electrode is cut into 5.0cm×3.0cm, and the composite body with an insulating layer on the negative electrode is cut into 5.2cm×3.2cm, and the pole ears are welded on each. The positive electrode and the composite body are overlapped in such a way that the positive electrode active material layer and the insulating layer are in contact with each other to obtain a laminate. The electrolyte is impregnated into the laminate and sealed in the outer packaging material of the aluminum laminate film. Hot pressing (85°C, 0.5MPa, 2 minutes) is performed from the outer packaging material to bond the electrode and the insulating layer to obtain a battery. As the electrolyte, 1mol / L LiPF6-ethylene carbonate: ethyl methyl carbonate (mass ratio is 3:7) is used. The set capacity of the battery is 40mAh (range of 4.2V-2.5V).

[0385] [Examples 102 to 109, Comparative Examples 101 to 103]

[0386] Each battery was produced in the same manner as in Example 101, except that the material, composition and thickness of the insulating layer were set to the specifications listed in Table 2.

[0387] The PVDF-based resin (B) used in Example 106 and the like is a VDF-HFP-acrylic acid terpolymer in which the ratio of HFP to all polymer components is 5.7 mol % and the ratio of acrylic acid to all polymer components is 0.8 mol %.

[0388] The PVDF-based resin (C) used in Comparative Example 103 is a VDF-HFP binary copolymer in which the ratio of HFP to all polymer components is 2.5 mol %.

[0389] In Example 105 and Example 109, magnesium hydroxide particles and barium sulfate particles were used at a ratio of magnesium hydroxide particles to barium sulfate particles = 50:50 (mass ratio).

[0390] [Reference Example 101]

[0391] -Production of a 3-layer diaphragm-

[0392] Using a reverse roll coater, an equal amount of coating liquid (A) was applied to both sides of a polyethylene microporous membrane (thickness 7 μm, porosity 36%, Gurley value 120 seconds / 100 mL). The membrane was immersed in a coagulation liquid (DMAc: water = 50:50 (mass ratio), liquid temperature 40°C) to solidify the coating layer, and then washed in a water washing tank at a water temperature of 40°C and dried. As described above, a separator having a coating layer formed on both sides of the polyethylene microporous membrane was obtained.

[0393] -Battery production-

[0394] The positive electrode and negative electrode of Example 101 were prepared. The positive electrode was cut into 5.0 cm×3.0 cm, and the negative electrode was cut into 5.2 cm×3.2 cm, and electrode tabs were welded to each. The separator was cut into 5.4 cm×3.4 cm.

[0395] The positive electrode, the separator, and the negative electrode are stacked in the order of the positive electrode, the separator, and the negative electrode so that the electrode active material layer is in contact with the separator. The electrolyte (the same electrolyte as that used in Example 101) is impregnated in the stack and sealed in the outer packaging material of the aluminum laminate film. Hot pressing (85°C, 0.5 MPa, 2 minutes) is performed from the outer packaging material to bond the electrode and the separator to obtain a battery.

[0396] Table 2 shows the composition, physical properties, and evaluation results of each battery of Examples 101 to 109, Comparative Examples 101 to 103, and Reference Example 101.

[0397] [Table 2]

[0398]

[0399] <<Manufacturing of non-aqueous secondary battery of the third embodiment>>

[0400] [Example 201]

[0401] -Making the positive electrode-

[0402] 94 parts by mass of lithium cobalt oxide powder, 3 parts by mass of acetylene black, 3 parts by mass of polyvinylidene fluoride resin, and an appropriate amount of N-methyl-2-pyrrolidone were kneaded to prepare a slurry. The slurry was coated on an aluminum foil with a thickness of 20 μm, and pressed after drying to obtain a positive electrode (single-sided coating, unit area weight of 20.5 mg / cm 2 , density is 2.95g / cm 3 ).

[0403] - Fabrication of negative electrode -

[0404] 96.2 parts by mass of graphite powder, 2.8 parts by mass of a modified styrene-butadiene copolymer, 1.0 parts by mass of carboxymethyl cellulose, and an appropriate amount of water were kneaded to prepare a slurry. The slurry was coated on a copper foil having a thickness of 15 μm, and after drying, it was pressed to obtain a negative electrode (single-sided coating, unit area weight of 10.0 mg / cm 2 , density is 1.60g / cm 3 ).

[0405] -Insulation layer production-

[0406] A VDF-HFP binary copolymer (the proportion of HFP in all polymer components is 2.4 mol%) is dissolved in a mixed solvent of dimethylacetamide (DMAc) and tripropylene glycol (TPG) (DMAc:TPG=80:20 [mass ratio]) in a concentration of 5 mass%, and then barium sulfate particles (average primary particle size of 0.05 μm) are added and stirred to obtain a coating liquid (201). The mass ratio of the VDF-HFP binary copolymer to the barium sulfate particles (VDF-HFP binary copolymer: barium sulfate particles) is 20:80.

[0407] The coating liquid (201) was applied to the active material layer of the negative electrode using a knife coater. It was immersed in a coagulation liquid (DMAc: water = 50:50 (mass ratio), liquid temperature was 25°C) for 5 minutes to solidify the coating layer, and then washed in a water washing tank with a water temperature of 25°C for 1 minute. It was lifted out of the water washing tank and placed in a constant temperature bath at 70°C, dried for 15 minutes, and then dried under reduced pressure at 110°C for 3 hours. As described above, a composite having a single insulating layer arranged on the negative electrode was obtained.

[0408] -Battery production-

[0409] The positive electrode is cut into 5.0cm×3.0cm, and the composite body with an insulating layer on the negative electrode is cut into 5.2cm×3.2cm, and the pole ears are welded on each. The positive electrode and the composite body are overlapped in such a way that the positive electrode active material layer and the insulating layer are in contact with each other to obtain a laminate. The electrolyte is impregnated into the laminate and sealed in the outer packaging material of the aluminum laminate film. Hot pressing (85°C, 0.5MPa, 2 minutes) is performed from the outer packaging material to bond the electrode and the insulating layer to obtain a battery. As the electrolyte, 1mol / L LiPF6-ethylene carbonate: ethyl methyl carbonate (mass ratio is 3:7) is used. The set capacity of the battery is 40mAh (range of 4.2V-2.5V).

[0410] [Examples 202 to 207, Comparative Examples 201 to 206]

[0411] The same operation as in Example 201 was carried out, wherein the material, composition and thickness of the insulating layer were set to the specifications listed in Table 3 to manufacture each battery.

[0412] [Reference Example 201]

[0413] -Production of a 3-layer diaphragm-

[0414] Using a reverse roll coater, an equal amount of the coating liquid (201) was applied to both sides of a polyethylene microporous membrane (thickness 7 μm, porosity 36%, Gurley value 120 seconds / 100 mL). The membrane was immersed in a coagulation liquid (DMAc: water = 50:50 (mass ratio), liquid temperature 40°C) to solidify the coating layer, and then washed in a water washing tank at a water temperature of 40°C and dried. As described above, a separator having a coating layer formed on both sides of the polyethylene microporous membrane was obtained.

[0415] -Battery production-

[0416] The positive electrode and negative electrode of Example 201 were prepared. The positive electrode was cut into 5.0 cm×3.0 cm, and the negative electrode was cut into 5.2 cm×3.2 cm, and electrode tabs were welded to each. The separator was cut into 5.4 cm×3.4 cm.

[0417] The positive electrode, the separator, and the negative electrode are stacked in the order of the positive electrode, the separator, and the negative electrode so that the electrode active material layer is in contact with the separator. The electrolyte (the same electrolyte as that used in Example 201) is impregnated in the stack and sealed in the outer packaging material of the aluminum laminate film. Hot pressing (85°C, 0.5MPa, 2 minutes) is performed on the outer packaging material to bond the electrode and the separator to obtain a battery.

[0418] Table 3 shows the composition, physical properties, and evaluation results of each battery of Examples 201 to 207, Comparative Examples 201 to 206, and Reference Example 201.

[0419] [Table 3]

[0420]

[0421] The entire disclosure of Japanese application No. 2020-127692 filed on July 28, 2020 is incorporated into this specification by reference. The entire disclosure of Japanese application No. 2020-127693 filed on July 28, 2020 is incorporated into this specification by reference. The entire disclosure of Japanese application No. 2020-127694 filed on July 28, 2020 is incorporated into this specification by reference.

[0422] All documents, patent applications, and technical standards described in this specification are incorporated into this specification by reference to the same extent as if each document, patent application, and technical standard was specifically and individually described.

Claims

1. A non-aqueous secondary battery comprising: positive electrode; negative electrode; an insulating layer, the insulating layer being a single layer having one surface in contact with the positive electrode and the other surface in contact with the negative electrode, and containing a polyvinylidene fluoride resin and inorganic particles; and Electrolyte, The content of the polyvinylidene fluoride resin contained in the insulating layer is 100 mass %, based on the total amount of all resins contained in the insulating layer. The weight average molecular weight of the polyvinylidene fluoride resin contained in the insulating layer is 900,000 to 1,500,000. The mass ratio of the inorganic particles in the insulating layer is 50 mass % or more and less than 90 mass %, The average primary particle size of the inorganic particles is 0.02 μm or more, The inorganic particles include at least one selected from the group consisting of metal hydroxide particles and metal sulfate particles.

2. A non-aqueous secondary battery comprising: positive electrode; negative electrode; An insulating layer, the insulating layer being a single layer having one side in contact with the positive electrode and the other side in contact with the negative electrode, and comprising a polyvinylidene fluoride resin and inorganic particles, wherein the polymer components of the polyvinylidene fluoride resin include vinylidene fluoride and a monomer represented by the following general formula (1); and Electrolyte, [Chemical formula 1] In the general formula (1), R 1 , R 2 and R 3 Each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 5 carbon atoms, a carboxyl group, or -C(=O)-OR 4 ,in, R 4 represents an alkyl group having 1 to 5 carbon atoms, X represents a single bond, an alkylene group having 1 to 5 carbon atoms, or an alkylene group having 1 to 5 carbon atoms having a substituent, and Y represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an alkyl group having 1 to 5 carbon atoms substituted with at least one hydroxyl group, an alkyl group having 1 to 5 carbon atoms substituted with at least one carboxyl group, or -ROC(=O)-(CH2) n -C(=O)-OH, wherein R represents an alkylene group having 1 to 5 carbon atoms, and n represents an integer greater than 0, The content of the polyvinylidene fluoride resin contained in the insulating layer is 100 mass %, based on the total amount of all resins contained in the insulating layer. The average primary particle size of the inorganic particles is 0.02 μm or more, The inorganic particles include at least one selected from the group consisting of metal hydroxide particles and metal sulfate particles.

3. A non-aqueous secondary battery comprising: positive electrode; negative electrode; an insulating layer, the insulating layer being a single layer having one surface in contact with the positive electrode and the other surface in contact with the negative electrode, and containing a polyvinylidene fluoride resin and inorganic particles; and electrolyte, the thickness of the insulating layer is 5 μm or more and 30 μm or less, The content of the polyvinylidene fluoride resin contained in the insulating layer is 100 mass %, based on the total amount of all resins contained in the insulating layer. The inorganic particles include metal sulfate particles, The average primary particle size of the inorganic particles is 0.02 μm or more.

4. The nonaqueous secondary battery according to claim 1 or claim 2, wherein: The average primary particle size of the inorganic particles included in the insulating layer is 0.02 μm or more and less than 1.00 μm.

5. The nonaqueous secondary battery according to claim 1 or claim 2, wherein: The thickness of the insulating layer is not less than 5 μm and not more than 30 μm.

6. The nonaqueous secondary battery according to any one of claims 1 to 3, wherein The porosity of the insulating layer is greater than 40% and less than 80%.

7. The nonaqueous secondary battery according to any one of claims 1 to 3, wherein The mass per unit area of ​​the insulating layer is 4 g / m 2 Above and less than 40g / m 2 .

8. The nonaqueous secondary battery according to claim 3, wherein The metal sulfate particles have an average primary particle size of 0.02 μm or more and 1.00 μm or less.

9. The nonaqueous secondary battery according to claim 2 or claim 3, wherein: The mass ratio of the inorganic particles in the insulating layer is 50 mass % or more and less than 90 mass %. 10 . The nonaqueous secondary battery according to claim 1 , wherein an electromotive force is obtained by doping and dedoping of lithium ions.

Citation Information

Patent Citations

  • JP1974088972A

  • Hyojihoho

    JP1976029895A

  • Automatic sample feeder of liquid chromatography

    JP1983080555A

  • Waste burning and disposing device

    JP1984038523A

  • Electrode sheet for non-aqueous electrolyte battery,method of manufacturing the same, and non-aqueous electrolyte secondary battery using the sheet

    JP2010056037A